Impulsive discontinuous hyperbolic partial differential equationsof fractional order on Banach algebras - Said Abbas (Electronic Journal of Differential Equations, 2010)
This article studies the existence of solutions and extremal solutions to partial hyperbolic differential equations of fractional order with impulses in Banach algebras under Lipschitz and Caratheodory conditions and certain monotonicity conditions.